2014
DOI: 10.1371/journal.pone.0107739
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Lifetime Suicide Attempts and Schizotypal Traits in Patients with Schizophrenia

Abstract: Patients with schizophrenia are at increased risk for suicide. Various risk factors for suicide have been reported in schizophrenia; however, few studies have examined the association between personality traits and suicidal behavior. We administered the Schizotypal Personality Questionnaire (SPQ) to 87 Japanese patients with schizophrenia (49 males; mean age 38.1±10.6 years) with and without a history of suicide attempts (SA and nSA groups, respectively), and 322 controls (158 males; mean age 40.8±13.9 years).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
2
14
1
Order By: Relevance
“…Eight subjects were excluded due to Axis I pathology, 10 subjects were excluded due to personal history of head trauma or neurological conditions, and another three subjects dropped out; therefore the final sample consisted of 200 participants (89 males/111 females, age mean± SD = 29.80± 9.69 years, age range = 18-57 years). The total SPQ score (mean± SD) of the entire sample was 18.98± 13.20 (range = 0-61), similar to published general population studies in which subjects with objectively determined psychopathology were excluded, as in the present study Hori et al, 2013;Noguchi, Hori, & Kunugi, 2008;Rossi & Daneluzzo, 2002;Teraishi et al, 2014). The present study was part of the Prefrontally Mediated Endophenotypes in the Schizophrenia Spectrum (PreMES) study.…”
Section: Methodssupporting
confidence: 78%
“…Eight subjects were excluded due to Axis I pathology, 10 subjects were excluded due to personal history of head trauma or neurological conditions, and another three subjects dropped out; therefore the final sample consisted of 200 participants (89 males/111 females, age mean± SD = 29.80± 9.69 years, age range = 18-57 years). The total SPQ score (mean± SD) of the entire sample was 18.98± 13.20 (range = 0-61), similar to published general population studies in which subjects with objectively determined psychopathology were excluded, as in the present study Hori et al, 2013;Noguchi, Hori, & Kunugi, 2008;Rossi & Daneluzzo, 2002;Teraishi et al, 2014). The present study was part of the Prefrontally Mediated Endophenotypes in the Schizophrenia Spectrum (PreMES) study.…”
Section: Methodssupporting
confidence: 78%
“…Previous studies have reported no association between suicidal behavior and positive or negative symptoms 29). Previously, it was reported that there was no association between the delusions and other psychotic symptoms and the history of suicide attempts in patients with schizophrenia 30,31). In contrast, it has been reported that command hallucinations could be a risk factor for suicide attempts 32).…”
Section: Discussionmentioning
confidence: 98%
“…behavior (Joiner et al, 2001;Kwapil et al, 2013;Teraishi et al, 2014;Jahn et al, 2016). Based on the assumption that individuals with high suicide risk question their life's value and have lost the desire to find their life's meaning, it is thought that people with less meaningfulness are at increased risk of having serious suicidal thoughts and attempts (Zhao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%